Small cell neuroendocrine carcinoma: a rare second primary malignancy after treatment of nasopharyngeal carcinoma - Madhusudhan, Krishnamoorthy; Hassan, Nor Eyzawiah; Md Shukri, Norasnieda; Hitam, Shahrul; Bakrin, Ikmal Hisyam (Sciendo, 2018)
Small cell neuroendocrine carcinoma (SCNEC) of the nasopharynx and nasal cavity is a rare condition. It is an aggressive malignancy with a high recurrence rate. Despite its rarity in the sinonasal region, it may occur as a second primary malignancy. Patients with cancer of the head and neck region are more prone to develop a second primary tumor due to the field cancerization phenomenon, and a higher incidence is seen in those who have previously received radiation therapy. A detailed clinical and histopathological examination is pivotal to diagnose SCNEC as a second primary malignancy. We wish to highlight such a peculiar case from our center.